In memoriam: Sajio Sumida (July 06th, 1933 – November 01st, 2017) - Problems of Cryobiology; Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1):098–099